Contamination status and associated ecological risk assessment of heavy metals in different wetland sediments from an urbanized estuarine ecosystem. (December 2022) - Hossain, M. Belal; Rahman, M. Asrafur; Hossain, Md. Kamal; Nur, As-Ad Ujjaman; Sultana, Salma; Semme, Sanjida; Albeshr, Mohammed Fahad; Arai, Takaomi; Yu, Jimmy
Abstract: Sediment samples of different wetland types (saltmarsh, mangrove, tidal pool, mudflat and sandflat) from an urbanized estuary were analyzed to evaluate the contamination level and ecological risks of five heavy metals (Pb, Fe, Zn, Ni and Cr). The findings showed that the mean concentration (mg/kg) of heavy metals followed the order of Fe > Zn > Ni > Pb > Cr, while Pb and Fe concentrations exceeded the recommended guidelines. Heavy metals levels were highest in saltmarsh and mudflats. Contamination assessment indices e.g., contamination factor (CF), degree of contamination (CD), enrichment factor (EF), and geo-accumulation index (Igeo) revealed that the studied wetlands had low to moderate levels of pollution, meaning these sites receive medium levels of anthropogenic contamination compared with background values. For some of the studied metals, such as Pb, Zn, Fe, and Ni, the EF value was >1 in certain types of wetland, indicating anthropogenic sources, while Cr was <1 indicating natural sources. The pollution load index (PLI) value was determined to be <1, indicating perfection of soil, and was in the following order: mudflat> saltmarsh> tidal pool> mangrove > sandflat. The ecological risk (RI) value was the highest for saltmarsh and the lowest for sandflats. However, the RI value for Cr, Zn, Ni, and Pb was <30 suggesting that these metals pose a low risk in the local ecosystem. Cluster analysis (CA), principal component analysis (PCA), and Pearson's correlation specified that anthropogenic sources of metals. Graphical abstract: Unlabelled Image Highlights: Sediments of wetlands (e.g. tidal pool, saltmarsh) were firstly analyzed for metal. The mean concentration (mg/kg) followed the order of Fe > Zn > Ni > Pb > Cr Mudflat and saltmarshes accumulated highest levels of heavy metals. The ecological risk value was the highest for saltmarsh and the lowest for sandflats. EF value for Pb, Zn, Fe, and Ni was >1 indicating anthropogenic origin.